SYSTEM OF THE AUTOMATED CHECKING OLYMPIC SOLUTIONS UNIVERSAL OLYMP CHECKER V.1.1. - I. Alekseichuk (Kherson State University, 2009)
Article is devoted a problem of creation of system of the automated testing olympiad problems. The overall objective of the given report - to share experience in working out and introduction of software for automatic checking.